Financial Literacy for the Students in Christian Senior High School 1 of BPK Penabur in Cirebon to Prepare Them to be the Intelligent Investors - Herlina Herlina; Bram Hadianto; Ika Gunawan; Peter Peter; Martalena Martalena; Dini Iskandar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Financial literacy is helpful for learners to recognize the features of the capital market and their instruments. With this knowledge, they are expected to manage their money wisely, especially in selecting the devices. Furthermore, to realize this condition, this service to the community aims to measure this literacy level and recognize risk profiles. The methods utilized in this service are lecture, discussion, and simulation. The participants in this service are the 40 students in the eleventh grade taking social science in the Christian senior high school 1 of BPK Penabur in Cirebon. Also, the precise answers of the students based on financial literacy items are used to evaluate this service. Surprisingly, the correct answers to these basic and advanced items are from 60.53% to 78.95% and 63.16% to 78.95%, respectively, indicating the middle financial level exists. This level is above the national literacy level in 2019 in Indonesia: 38.03%. Besides, related to the risk profile, most students are conservative (47.5%) and moderate (47.5%). Based on this outcome, the students with a conventional risk profile are expected to invest their money in a time-deposit account, government bonds, and fixed-income and money-market mutual funds. Meanwhile, students with a moderate risk profile should place their funds in blue-chip stocks and mixed mutual funds.